Anno de 1747. Missão da China; e Jgreja de N. Senhora do Amparo. (1747)
This abstract describes a composite historical transcription comprising administrative, ecclesiastical, and diplomatic records from Macau, spanning February to July 1747, with marginalia and supplementary entries extending to 1749. The documents—drawn from the archives of the Leal Senado (Municipal Council), the Jesuit College of St Joseph, Dominican and Franciscan convents, and the Procurator’s Office—detail intergovernmental and interconfessional tensions surrounding the Church of Our Lady of Amparo (Nossa Senhora de Amparo) in Macau and its relationship to Qing imperial authority. Key figures include Severino de Carvalho de Moraes and Jerónimo de Carvalho de Morais (S.J.), Procurators of the Senate; Father Francisco, Father João Francisco Dias (O.P.), Father Luís de Siqueira (S.J., Provincial of China), and Fr. Oliva (O.F.M.); mandarins of Anjão, Apanhão, and Canton; and Governor Damião Pereira Pinho. Central subjects encompass the reception and translation of Qing edicts (*chapás*), jurisdictional disputes over missionary access to Fujian and Jiangxi provinces, the detention and corporal punishment of missionaries within Qing territory, the contested ownership and physical integrity of the Church of Our Lady of Amparo, the transfer of its sacred furnishings to the Dominican College, debates over Portuguese civic versus ecclesiastical authority, and the complex roles of the Congregation for the Propagation of the Faith, the Society of Jesus, and local Macanese governance. The records reflect the precarious position of Catholic missions under Qing restrictions, Macau’s intermediary status, and the entanglement of religious, diplomatic, and fiscal concerns in Sino-Portuguese relations.
Keywords: China; Diplomatic Records from Macau; Dominican Convent Records; Ecclesiastical Administration in Macau; Franciscan Convent Records; Interconfessional Tensions in Qing China; Jesuit College of St Joseph Archives; Leal Senado Municipal Archives; Procurator’s Office Documentation; Transcription